Renal sympathetic denervation improves pressure-natriuresis relationship in cardiorenal syndrome: insight from studies with Ren-2 transgenic hypertensive rats with volume overload induced using aorto-caval fistula - Honetschlägerová, Zuzana; Husková, Zuzana; Kikerlová, Soňa; Sadowski, Janusz; Kompanowska-Jezierska, Elzbieta; Táborský, Miloš; Vaňourková, Zdenka; Kujal, Petr; Červenka, Luděk (Hypertension research, 2024)
The aim was to evaluate the effects of renal denervation (RDN) on autoregulation of renal hemodynamics and the pressure-natriuresis relationship in Ren-2 transgenic rats (TGR) with aorto-caval fistula (ACF)-induced heart failure (HF). RDN was performed one week after creation of ACF or sham-operation. Animals were prepared for evaluation of autoregulatory capacity of renal blood flow (RBF) and glomerular filtration rate (GFR), and of the pressure-natriuresis characteristics after stepwise changes in renal arterial pressure (RAP) induced by aortic clamping. Their basal values of blood pressure and renal function were significantly lower than with innervated sham-operated TGR (p < 0.05 in all cases): mean arterial pressure (MAP) (115 ± 2 vs. 160 ± 3 mmHg), RBF (6.91 ± 0.33 vs. 10.87 ± 0.38 ml.min-1.g-1), urine flow (UF) (11.3 ± 1.79 vs. 43.17 ± 3.24 µl.min-1.g-1) and absolute sodium excretion (UNaV) (1.08 ± 0.27 vs, 6.38 ± 0.76 µmol.min-1.g-1). After denervation ACF TGR showed improved autoregulation of RBF: at lowest RAP level (80 mmHg) the value was higher than in innervated ACF TGR (6.92 ± 0.26 vs. 4.54 ± 0.22 ml.min-1.g-1, p < 0.05). Also, the pressure-natriuresis relationship was markedly improved after RDN: at the RAP of 80 mmHg UF equaled 4.31 ± 0.99 vs. 0.26 ± 0.09 µl.min-1.g-1 recorded in innervated ACF TGR, UNaV was 0.31 ± 0.05 vs. 0.04 ± 0.01 µmol min-1.g-1 (p < 0.05 in all cases). In conclusion, in our model of hypertensive rat with ACF-induced HF, RDN improved autoregulatory capacity of RBF and the pressure-natriuresis relationship when measured at the stage of HF decompensation.
Keywords: sympatektomie; Blood Pressure; Renal Circulation; Hypertension; Renal autoregulation; Renal blood flow; Heart Failure; zvířata; Sympathectomy; Rats; Glomerular Filtration Rate; Kidney; ledviny; Cardio-Renal Syndrome; sodium excretion; Volume-overload heart failure; Fistula; hypertenze; Natriuresis; renální oběh; píštěle; krysa rodu Rattus; kardiorenální syndrom; Ren-2 transgenic hypertensive rat; potkani transgenní; Animals; srdeční selhání; hodnoty glomerulární filtrace; natriuréza; krevní tlak; Rats, Transgenic